Maternal age and the risk of low birthweight and pre-term delivery: a pan-Nordic comparison. (9th November 2022) - Aradhya, Siddartha; Tegunimataka, Anna; Kravdal, Øystein; Martikainen, Pekka; Myrskylä, Mikko; Barclay, Kieron; Goisis, Alice
Abstract: Background: Advanced maternal age at birth is considered a risk factor for adverse birth outcomes. A recent study applying a sibling design has shown, however, that the association might be confounded by unobserved maternal characteristics. Methods: Using total population register data on all live singleton births during the period 1999–2012 in Denmark ( N  = 580 133; 90% population coverage), Norway ( N  = 540 890) and Sweden ( N  = 941 403) and from 2001–2014 in Finland ( N  = 568 026), we test whether advanced maternal age at birth independently increases the risk of low birthweight (LBW) (<2500 g) and pre-term birth (<37 weeks gestation). We estimated within-family models to reduce confounding by unobserved maternal characteristics shared by siblings using three model specifications: Model 0 examines the bivariate association; Model 1 adjusts for parity and sex; Model 2 for parity, sex and birth year. Results: The main results (Model 1) show an increased risk in LBW and pre-term delivery with increasing maternal ages. For example, compared with maternal ages of 26–27 years, maternal ages of 38–39 years display a 2.2, 0.9, 2.1 and 2.4 percentage point increase in the risk of LBW in Denmark, Finland, Norway and Sweden, respectively. The same patterns hold for pre-term delivery. Conclusions: Advanced maternal age is independently associated with higher risk of poor perinatal health outcomes even after adjusting for all observed and unobserved factors shared between siblings.